To Belong to the Living – om queer slægtskab og reproduktiv futurisme - Petersen, Michael Nebeling (Kvinder, Køn & Forskning, 2013)
Following Lee Edelman’s polemic argument against reproductive futurism and Sara Ahmed’s thinking on queer attachments, this article discusses queer kinship, as it is represented in the American movie The Kids Are All Right (2010). The reading argues that a heteronormative temporal development of the children makes queer kinship recognizable inside a heteronormative kinship paradigm, while simultaneously one mother and the sperm donor fight about the brutal reconceptualizations of masculinity, kinship, and queerness. The closing discussion of the concept of reproductive futurism departs from José Estaban Muñoz’ critique of Edelman and from the foucauldian concept of racism as the death function in the economy biopolitics and argues that race disappears in the thinking of Edelman, but has a significant part in the configuration of kinship in The Kids Are All Right .